The effects of Chinese learners’ English acoustic-prosodic patterns on listeners’ attitudinal judgments - Chen, Hsueh Chu; Wang, Qian (Penerbit Universiti Kebangsaan Malaysia, 2016)
Prosody has been emphasised in second language (L2) pedagogy as a strong contribution to successful intercultural communication. As English and Chinese are typologically different languages (Chinese is a syllable-timed language while English a stress-timed language), many differences in stress and rhythmic patterns trouble Chinese learners of English. This study analyses acoustic speech samples for 13 prosodic features collected from 16 Chinese L2 learners and examines the relative importance of various prosody features on language attitudes that native and non-native English listeners hold towards Chinese-accented speech. The results revealed that Chinese speakers have a relatively slow speech rate and produce more stressed words in their English speech compared with native English speakers. When listeners heard long and inappropriate silent pauses in the speech, the integrity rating of the speakers decreased. The speech rate contributed significantly to both attractiveness rating and competence rating. That is, listeners evaluated speakers as more competent and attractive if the latter spoke faster.